Nosocomial infections in "Dr. Salvador Allende" Hospital, Havana, february to June of 2015 period - Lorena Monté Cerero; Raiza Martínez Casanueva (Universidad de Ciencias Médicas de La Habana, 2017)
Introduction:Infections constitute a frequent chief complaint in hospital services and, because of their seriousness, they sometimes lead to patients´ admissions.  In other cases, they are hospital-acquired infections which considerably increase nosocomial morbidity and mortality.  Generally, the most frequently isolated microorganisms in hospitals are: Staphylococcus aureus, Enterococcus spp, the non-fermenting bacilli, and enterobacteria.  Objective: To determine the most frequent microorganisms and isolation areas in samples used for a microbiological study, taken from patients admitted to "Salvador Allende" Hospital of Havana, during the February-June period 2015.  Material and Methods: A descriptive cross- sectional study was conducted to determine the most frequent microorganisms and isolation areas in the in samples used for a microbiological study, taken from admitted patients during the period mentioned. The information about the identification of microorganisms and the type of sample were both obtained from the records of the Microbiology Laboratory of the hospital; the absolute and relative frequencies were calculated; and the results were tabulated. Results: During the period studied, the most isolated microorganisms were: E. coli, non- fermenting bacilli, S. aureus, and Enterobacter spp. Regarding the isolation areas, the most frequent ones were the skin, the urine, the respiratory system, and the blood.  Conclusions: The predominance of gram-negative microorganisms was evident, being the E. coli, the most frequent of them. Keywords:Cuba, E. coli, S. aureus, non-fermenting bacilli, microorganisms, isolation areas